The Impact of Coworking Spaces on the Wellbeing of Parenting Mothers : A Case Study of Jahoda Coworking - Šrámková, Kateřina; Orel, Marko, 1986-; Šlapáková Losová, Veronika; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis explores the impact of coworking spaces on working mothers' well-being and work-life balance. It acknowledges the challenges mothers face in balancing career and family, particularly the lack of childcare options in Prague. The research investigates how coworking spaces, like Jahoda, can address these challenges by offering a flexible and supportive work environment. Through semi-structured interviews and ethnographic research at Jahoda, the study examines how working mothers perceive the impact of the coworking space on their well-being, work-life balance, and productivity. The core research questions focus on how Jahoda contributes to these aspects for working mothers. The space offers flexibility, on-site childcare, and community options so mothers can feel less lonely. This reduces stress, improves work-life balance, and increases well-being for working mothers.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses